GAMBARAN DUKUNGAN SUAMI TERHADAP DETEKSI DINI KANKER SERVIKS DI DESA TUMBAK BAYUH WILAYAH KERJA PUSKESMAS MENGWI II BADUNG - Dewi, Rai Rosita Candra; Astuti, Ika Widi; Pramitaresthi, I Gusti Ayu (Coping: Community of Publishing in Nursing, 2022)
Cervical cancer is the second killer cancer of women after breast cancer. The high mortality rate due to cervical cancer is caused by the low coverage of cervical cancer screening. One of the factors that influence cervical cancer screening is the husband’s support. This research aims to describe the husband’s support for cervical cancer screening. It was descriptive quantitative research. It applied the purposive sampling technique with a sample of 100 respondents. The data were collected using an online questionnaire and analyzed using univariate analysis. The results obtained that respondents who had done cervical cancer screening were 72%, but only 30% did it routinely. Husband’s support for cervical cancer screening was in a good category, namely 72%. It consists of four sub-sections. It was the informational support in the poor category (77%) and the rest were assessment support (65%), emotional support (81%), and instrumental support (83%) in the good category. The conclusion is most of the respondents had done their cervical cancer screening, but most of them did it not routinely. Husband’s support for cervical cancer screening was mostly in the good category. Education regarding cervical cancer screening's importance to prevent morbidity and mortality of cervical cancer, should not only targets women but also their husbands. Thus, husbands can provide support to their wives to do cervical cancer screening regularly.